2021
DOI: 10.20883/medical.e523
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of different dietary strategies in the management of obesity and obesity-related comorbidities

Abstract: The prevalence of obesity has been increasing worldwide; however, the optimal dietary strategy for improving anthropometric and cardiometabolic parameters remains unknown. This review discusses the effectiveness of popular diets in the management of obesity and obesity-related comorbidities. The differences among popular diets are small and associated with dietary adherence and caloric intake. The Mediterranean diet is most effective in facilitating weight loss and improving cardiometabolic parameters, althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…As epidemiological studies have shown an incompatible association between ovarian cancer and indicated that obesity and severe obesity increase the risk of ovarian cancer [8]. Even though it is found that the effectiveness of different dietary strategies in the management of obesity and obesity-related complications have shown heterogeneous findings, none of our patients was on diet [9].…”
Section: Introductionmentioning
confidence: 69%
“…As epidemiological studies have shown an incompatible association between ovarian cancer and indicated that obesity and severe obesity increase the risk of ovarian cancer [8]. Even though it is found that the effectiveness of different dietary strategies in the management of obesity and obesity-related complications have shown heterogeneous findings, none of our patients was on diet [9].…”
Section: Introductionmentioning
confidence: 69%